Analisis Gaya Bahasa dan Majas pada Lirik Lagu “Sampai Jadi Debu” Karya Banda Neira - Annisa Mazaya Fhatarani; Mirza Irdina (Jurnal Pendidikan Bahasa dan Anak Usia Dini, 2025)
This article contains an analysis of the language style and figures of speech in the lyrics of the song "Sampai Jadi Debu" by Banda Neira. The discussion in this article focuses on the diction aspect of connotation and the use of figures of speech contained in the song's lyrics. The research method used to analyze the song lyrics is a qualitative descriptive method. The analysis carried out shows that the diction contained in the song lyrics is connotative. The connotative diction used in the song's lyrics is a manifestation of the creative thoughts of the songwriter when creating the lyrics for his songs. Apart from that, the song's lyrics use many figures of speech including metaphors, allegory figures of speech, and hyperbole figures of speech.